Perceived Stress and Employment Readiness Among Filipino Young Adults in Selected Higher Education Institutions in the Province of Cavite - Jervin Dinglasan Quicho; Dean Levi’s Geronimo Aquino; Keren Keisah Meredores Liquigan; Ancel Manlapas Rios (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Youths of working age often experience stress that may influence their preparedness to enter the workforce. This study aimed to examine the relationship between perceived stress and employment readiness among Filipino young adults enrolled in selected higher education institutions in the Province of Cavite. Understanding this relationship is important in identifying areas where students may require support as they transition from academic life to employment. The study employed a quantitative, descriptive correlational research design involving 555 participants determined through G*Power analysis. The respondents were Filipino young adults aged 18 to 24 who were full-time fourth- and fifth-year bachelor’s degree students enrolled during the first semester of Academic Year 2025–2026 in six selected higher education institutions located in Bacoor, Dasmariñas, and Imus, Cavite, and were selected through purposive sampling. Data were gathered using standardized instruments, namely the Perceived Stress Scale (PSS-10) developed by Sheldon Cohen to measure perceived stress and the Work Readiness Scale (WRS) developed by Caballero et al. (2011) to assess employment readiness. The collected data were analyzed using descriptive statistics, tests of normality, and correlational analysis to determine the association between the variables. The findings revealed that the majority of respondents exhibited moderate levels of perceived stress and moderate levels of employment readiness. Students demonstrated strengths in organizational skills and social competencies, while lower levels were observed in personal characteristics and practical work competencies.